2017
DOI: 10.1038/s41598-017-04913-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of MKKs and MAPKs from 16 legumes and detection of interacting pairs in chickpea divulge MAPK signalling modules

Abstract: The mitogen-activated protein kinase (MAPK)-mediated phosphorylation cascade is a vital component of plant cellular signalling. Despite this, MAPK signalling cascade is less characterized in crop legumes. To fill this void, we present here a comprehensive phylogeny of MAPK kinases (MKKs) and MAPKs identified from 16 legume species belonging to genistoid (Lupinus angustifolius), dalbergioid (Arachis spp.), phaseoloid (Glycine max, Cajanus cajan, Phaseolus vulgaris, and Vigna spp.), and galegoid (Cicer arietinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This indicates that MAPK signaling pathway is highly conserved among different legumes species. Purayannur et al [ 37 ] reported a direct interaction between CaMAPK3 and CaMAPK7 , indicating the potential for a direct interaction between MEK2 and MAPK20-1 in the present study. The up-regulation of MEK2 and MAPK20 -1 in CDC Robin further supports that these genes function together in MAPK signaling in this genotype.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…This indicates that MAPK signaling pathway is highly conserved among different legumes species. Purayannur et al [ 37 ] reported a direct interaction between CaMAPK3 and CaMAPK7 , indicating the potential for a direct interaction between MEK2 and MAPK20-1 in the present study. The up-regulation of MEK2 and MAPK20 -1 in CDC Robin further supports that these genes function together in MAPK signaling in this genotype.…”
Section: Resultssupporting
confidence: 67%
“…MEK2 has a function in protein phosphorylation during PAMP signaling and interacts with SNF-related kinase ( SNRK ) which was induced in all genotypes in the present study ( S5 Table ). Recently, MAPK signaling was characterized in multiple legume species [ 37 ]. Comparing the CDC Redberry sequences with the MAPK genes reported by Purayannur et al [ 37 ] in chickpea ( Cicer oreintanum ) and M .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAPK cascade pathway plays a pivotal role in plant development or stress response. In many species, the numbers of MAPKKK and MAPK are far more than MAPKK [29,41,42], the number of interaction pairs of MAPKKK-MAPKK and MAPKK-MAPK are also more than the number of MAPKK gene [42,43]. This results indicate that the number of MAPKK genes does not match the functional diversity of the MAPK cascade pathway.…”
Section: Discussionmentioning
confidence: 99%